ANALISIS PENGARUH PENGELUARAN PEMERINTAH DAN INVESTASI TERHADAP KESEMPATAN KERJA MELALUI PERTUMBUHAN EKONOMI - Harijono, Gatot Setio (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2013)
ABSTACT The Data from BKPMD Province of Bali describes the accumulated investment of 2006-2010 shows 62,20 percent of investment in the province of Bali is embedded in the tourism sector and 70,78 percent of them are foreign capital. Corresponding on dependency theory, this sort of thing could not give optimal impact on economic growth and employment. This study has the purpose to analyze the directly or indirectly effect of government expenditure and investment in Bali on employment throught economic growth, and also the effect of economic growth on employment in Bali. Main data of this study was quantitative panel from the entire city in Bali Province from 2006-2011. This study has used secondary data from the Directorate General of Treasury, Finance Bureau Province of Bali, and Bali Central Statistic Buerau with path analysis as tool of analysis. The result of the study shows in Province of Bali  1) government expenditure has significant effect on economic growth and employment. The efect of investment on through economic growth significant, but weak efect on employment, and economic growth has nonsignificant efect on employment.
Keywords: government expenditure, investment, economic growth, employment